Amending Agreement No.1 between the United Kingdom of Great Britain and Northern Ireland and the Republic of Moldova to amend the Strategic Partnership, Trade and Cooperation Agreement between the United Kingdom of Great Britain and Northern Ireland and the Republic of Moldova. Chisinau, 25 May 2023. ([2023-06-05]) - Unknown
No abstract available